United States, men in conversation at Utqiaġvik shop - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Group of men hanging out inside shop. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3